Construction of Co(OH)F/Ni(OH)2@Fe(OH)3 core-shell heterojunction on nickel foam for efficient oxygen evolution. (15th September 2022) - Jiu, Hongfang; Wei, Hao; Wang, Congli; Che, Sicong; Guo, Zhixin; Han, Yuxin; Xu, Qianwen; Yu, Xueqin; Zhang, Lixin
Abstract: The sluggish anodic reaction (OER) kinetics hinder electrochemical water splitting at high energy densities, which can be solved by developing suitable catalysts. Herein, we report a novel Co(OH)F/Ni(OH)2 @Fe(OH)3 -Dx (Dx represents the hydrolysis time, X = 0.5, 1, 2 days) heterojunction grown on nickel foam, which was synthesized by the hydrolysis of Fe 3+ on the Co(OH)F/Ni(OH)2 surface at room temperature. Electrocatalytic oxygen evolution tests showed that the prepared Co(OH)F/Ni(OH)2 @Fe(OH)3 -Dx composites had better catalytic activity than pure Co(OH)F/Ni(OH)2 in 1.0 M KOH, especially Co(OH)F/Ni(OH)2 @Fe(OH)3 -D1 . It only requires an ultra-low overpotential (η10 ) of 270 mV, SEM and TEM showed that Co(OH)F/Ni(OH)2 @Fe(OH)3 -D1 is a perfect all-encapsulated core-shell structure, which facilitates the exposure of active sites and electron transfer, and thus obviously improves oxygen evolution. Graphical abstract: Image 1 Highlights: Co(OH)F/Ni(OH)2 @Fe(OH)3 is prepared by hydrothermal and room temperature hydrolysis method. Co(OH)F/Ni(OH)2 @Fe(OH)3 -D1 formed a perfect fully coated core-shell structure. Co(OH)F/Ni(OH)2 @Fe(OH)3 -D1 showed outstanding OER activity.